SERUM BIOMARKERS FOR DETECTING ECTOPIC PREGNANCY - Rausch, Mary E (2012)
Unless an ectopic pregnancy is visible by ultrasound, diagnosis can be a challenge. Differentiating ectopic pregnancies from intrauterine pregnancies can be impossible without intervention or follow-up. This poses a clinical dilemma to the practitioner given the inherent danger to the mother of tubal rupture of an ectopic pregnancy versus the fear of intervening in the case of a desired pregnancy without certainty of diagnosis. Early diagnostic modalities are clearly lacking, and serum biomarkers are currently being investigated as a solution to need for a rapid and accurate test for ectopic pregnancy.